High-flame-retardancy powder coating for new energy automobile as well as preparation method and application of high-flame-retardancy powder coating
By using hydrothermal crystallization and spray pyrolysis methods to prepare layered double hydroxide nanocomposite flame retardant coated with silicon oxide in powder coatings for new energy vehicles, the problems of low flame retardant performance and toxicity of existing powder coatings are solved, and high flame retardant powder coatings with high oxygen index and fire resistance are achieved, supporting the safe development of new energy vehicles.
Patent Information
- Application Number
- CN202411925812.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The flame retardant performance of existing powder coatings for new energy vehicles is relatively low, and commonly used flame retardants will release toxic and harmful substances, making it difficult to meet the safety requirements of high-temperature and high-pressure environments of parts such as new energy vehicle battery packs.
A layered double hydroxide nanocomposite flame retardant coated with silica was prepared by two-step method of hydrothermal crystallization and spray pyrolysis. By optimizing raw material ratio and adjusting the type and dosage of flame retardant, a high flame retardant powder coating with high oxygen output index and good fire resistance is prepared.
It has realized the development of high flame retardant powder coatings for new energy vehicles, has excellent oxygen index and fire resistance, avoids the toxicity problem of traditional flame retardants, and provides technical support and safety guarantees for the rapid development and safe use of new energy vehicles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of powder coatings, and in particular relates to a highly flame-retardant powder coating for new energy vehicles, and a preparation method and application thereof. Background Art
[0002] As a new type of coating material, powder coating has many advantages in industrial production and civil building decoration. It has the advantages of saving resources and environmental protection, high surface hardness, rich colors and good effects, high construction efficiency, chemical resistance and weather resistance. It can be coated on the surface of various materials such as metal, plastic, ceramic, etc., so it is widely used in automobiles, furniture, construction, electrical appliances and other fields.
[0003] Consumers' recognition and acceptance of new energy vehicles have greatly increased, leading to a rapid growth in the production, sales and market share of new energy vehicles. However, during the driving of new energy vehicles, parts such as automotive battery packs will be affected by high temperatures and high pressures. Flame retardancy and fire resistance are safety properties that surface materials of parts such as new energy vehicle battery packs must possess. Among them, the use of highly flame-retardant powder coatings on parts such as battery packs can effectively reduce the occurrence of dangerous situations such as fires in accidents involving new energy vehicles, and is an important means to ensure the safety of new energy vehicles. However, common phosphorus-based flame retardants, nitrogen-based flame retardants, and halogen-based flame retardants have disadvantages such as low flame retardancy and the release of toxic and harmful substances after combustion.
[0004] Layered double hydroxides (LDHs) are a type of composite metal hydroxide with a layered structure. Their composition contains crystalline water, hydroxyl groups, etc., and have good flame retardant and smoke suppression properties. At the same time, silicon oxide can form a dense coating on the surface of the material, thereby preventing the coating from contacting the air. However, using them alone, it is impossible to obtain a highly flame retardant powder coating.
[0005] Therefore, there is an urgent need to develop a highly flame retardant powder coating for new energy vehicles, so as to provide technical support and safety guarantee for the rapid development and safe use of new energy vehicles. Summary of the invention
[0006] The purpose of the present invention is to provide a high flame retardant powder coating for new energy vehicles and a preparation method thereof, and a two-step method of hydrothermal crystallization and spray pyrolysis is adopted to obtain a silicon oxide-coated layered double hydroxide nanocomposite flame retardant. By improving the formula, optimizing the raw material ratio and adjusting the type and amount of the flame retardant, a high flame retardant powder coating with a high oxygen index and good fire resistance can be obtained, and the preparation method thereof is simple.
[0007] Another object of the present invention is to provide an application of a highly flame-retardant powder coating for new energy vehicles, which can be used for new energy vehicles, especially for battery boxes of new energy vehicles.
[0008] The specific technical solutions of the present invention are as follows:
[0009] A highly flame-retardant powder coating for new energy vehicles comprises the following raw materials in parts by weight: 80 to 150 parts of epoxy resin, 50 to 110 parts of unsaturated polyester resin, 15 to 50 parts of filler, 5 to 30 parts of flame retardant, 2 to 7.5 parts of pigment and 10 to 25 parts of auxiliary agent.
[0010] The mass ratio of the epoxy resin to the unsaturated polyester resin is (1-3):1;
[0011] The mass ratio of the filler to the epoxy resin is (1-3):10;
[0012] The epoxy resin is selected from E-12 epoxy resin;
[0013] The unsaturated polyester resin is selected from bisphenol A type unsaturated polyester;
[0014] The filler is selected from one of high-gloss calcium, high-gloss barium, and mica powder;
[0015] The mass fraction of the flame retardant is 2.5-12.5% of the total mass of the raw materials of the high flame retardant powder coating for new energy vehicles; the flame retardant is a silicon oxide-coated layered double hydroxide nano-composite flame retardant.
[0016] The composite nano flame retardant preparation method comprises the following steps:
[0017] 1) preparing a suspension of layered double hydroxide by a hydrothermal crystallization method;
[0018] 2) mixing the suspension with tetraethyl orthosilicate, sodium hydroxide, a surfactant, and a structure directing agent to obtain a mixed solution;
[0019] 3) spraying the mixed solution for pyrolysis and vacuum drying to obtain a silicon oxide-coated layered double hydroxide nanocomposite flame retardant.
[0020] Step 1) is specifically as follows: adding a metal source of layered double hydroxide into water, and then adding ammonia water to prepare the layered double hydroxide by hydrothermal crystallization;
[0021] In step 1), the layered double hydroxide is one of CoAl-LDHs, MgAl-LDHs and CaAl-LDHs;
[0022] In step 1), the temperature of the hydrothermal crystallization method is 150-220° C., and the hydrothermal reaction time is 12-24 hours;
[0023] In step 2), the volume ratio of the suspension to tetraethyl orthosilicate is 20:3, and the mass ratio of sodium hydroxide, surfactant and structure directing agent is 10:6:3;
[0024] In step 2), the dosage ratio of sodium hydroxide to tetraethyl orthosilicate is: 0.5-0.6 g / mL;
[0025] In step 2), the surfactant is F127; the structure directing agent is CTAB;
[0026] In step 3), the spray pyrolysis is specifically: ultrasonic atomization is used, the atomization frequency is 1.7 MHz, the power is 50 W, the micro-droplets generated by atomization are introduced into a tubular furnace for high-temperature pyrolysis treatment, the heating area length is 30 cm, the temperature is 600-800° C., and the powder is collected;
[0027] In step 3), the vacuum drying is carried out at a temperature of 100° C. and a vacuum drying time of 16 h.
[0028] The pigment is titanium dioxide or other powder pigments.
[0029] The mass fraction of the auxiliary agent is 4-15% of the total mass of the raw materials of the high flame retardant powder coating for new energy vehicles; the auxiliary agent includes at least three of a leveling agent, a defoaming agent, a brightening agent, a dispersant, and a curing agent, and the addition amount of each component in the auxiliary agent is the same.
[0030] The high flame retardant powder coating for new energy vehicles has an oxygen index of 46 to 55 and a GB14907 fire resistance of 1.12 to 1.35 hours.
[0031] The present invention provides a method for preparing a highly flame retardant powder coating for new energy vehicles, which is specifically:
[0032] Put the formulated amount of epoxy resin, unsaturated polyester resin, filler, flame retardant, pigment and additives into a mixing tank, fully stir and mix, extrude, disperse, dry, grind, sieve and classify to obtain a high flame retardant powder coating for new energy vehicles.
[0033] Wherein, in the extrusion molding, the screw speed of the extruder is controlled at 250-450 r / min, and the temperature is controlled at 95-120°C.
[0034] The invention provides an application of a highly flame-retardant powder coating for new energy vehicles, which is used for new energy vehicles, especially for battery boxes of new energy vehicles.
[0035] Compared with the prior art, the present invention adds a layered double hydroxide nanocomposite flame retardant coated with silicon oxide during the preparation of the powder coating, while ensuring that the various properties of the coating are not affected, thereby avoiding the problem that the added flame retardant seriously affects the conventional properties of the coating. The present invention can obtain a highly flame-retardant powder coating with a high oxygen index and good fire resistance by optimizing the raw material ratio and adjusting the type and amount of the flame retardant. The preparation method is simple, providing technical support and safety guarantee for the rapid development and safe use of new energy vehicles. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The unsaturated polyester resin used in the embodiments and comparative examples of the present invention is bisphenol A type unsaturated polyester resin: Changzhou Tianma Group Co., Ltd., TM-802; leveling agent: Huangshan Debang Powder Material Co., Ltd., TP3010; defoamer: Foshan Xinhuicheng Technology Co., Ltd., HC-36; brightener: Suzhou Jingyan New Material Co., Ltd., Ranbar OB-LA; dispersant: Foshan Xinhuicheng Technology Co., Ltd., K-513; curing agent: Huangshan Debang Powder Material Co., Ltd., TP1530. The ammonia water used is 28wt% ammonia water.
[0038] Example 1
[0039] A method for preparing a highly flame-retardant powder coating for new energy vehicles, specifically comprising:
[0040] According to mass parts, 150 parts of E-12 epoxy resin, 50 parts of unsaturated polyester resin, 15 parts of high gloss barium, 10 parts of SiO2-coated CoAl-LDHs nano-composite flame retardant, 5 parts of titanium dioxide and 10 parts of additives (the additives include leveling agent, defoamer, brightener, dispersant, curing agent, and each additive is equal) are put into a mixing tank and stirred thoroughly; then the evenly stirred raw materials are extruded through an extruder, the screw speed of the extruder is controlled to 450r / min, the temperature is controlled to 95°C, and a disperser is used for dispersion, and the dispersed powder coating is dried on a fluidized bed, and then ground with a grinder. After sieving and grading, a high flame retardant powder coating for new energy vehicles can be obtained.
[0041] The preparation method of the SiO2-coated CoAl-LDHs nanocomposite flame retardant used in Example 1 is:
[0042] 1) Dissolve cobalt nitrate and aluminum nitrate precursors in a mass ratio of 1:2 in 20 mL of deionized water, wherein the concentration of cobalt nitrate in deionized water is 1 mol / L, and then add 40 mL of 28 wt% ammonia water. Transfer the resulting solution into a high-pressure reactor with a polytetrafluoroethylene liner, and perform the hydrothermal crystallization at a temperature of 200 ° C. The hydrothermal reaction time is 24 h to obtain a suspension of CoAl-LDHs;
[0043] 2) Mix the suspension and tetraethyl orthosilicate in a volume ratio of 20:3, wherein 9 mL of tetraethyl orthosilicate, 5 g of sodium hydroxide, 3 g of F127 and 1.5 g of CTAB are added, and the mixture is stirred thoroughly.
[0044] 3) The obtained mixed solution was subjected to spray pyrolysis using ultrasonic atomization with an atomization frequency of 1.7 MHz and a power of 50 W. The micro-droplets generated by the atomization were introduced into a tubular furnace for high-temperature pyrolysis treatment. The heating area was 30 cm long and the temperature was 800°C. The powder was collected and vacuum dried at 100°C for 16 h to finally obtain SiO2-coated CoAl-LDHs nanocomposite flame retardant.
[0045] Example 2
[0046] A method for preparing a highly flame-retardant powder coating for new energy vehicles, specifically comprising:
[0047] According to mass parts, 80 parts of E-12 epoxy resin, 60 parts of unsaturated polyester resin, 20 parts of mica powder, 25 parts of SiO2-coated MgAl-LDHs nano-composite flame retardant, 5 parts of titanium dioxide and 25 parts of additives (the additives include leveling agent, defoamer, brightener, dispersant, curing agent, and each additive is equal) are put into a mixing tank and stirred thoroughly; then the evenly stirred raw materials are extruded into shape by an extruder, the screw speed of the extruder is controlled to 250r / min, the temperature is controlled to 100°C, and a disperser is used for dispersion, and the dispersed powder coating is dried on a fluidized bed, and then ground with a grinder, and a high flame retardant powder coating is obtained after sieving and grading.
[0048] The preparation steps of the SiO2-coated MgAl-LDHs nanocomposite flame retardant used in Example 2 are as follows:
[0049] 1) Dissolve magnesium nitrate and aluminum nitrate precursors in a mass ratio of 1:2 in 20 mL of deionized water, with a magnesium nitrate concentration of 1 mol / L; then add 40 mL of ammonia water, transfer the resulting solution into a high-pressure reactor with a polytetrafluoroethylene liner, and perform hydrothermal crystallization at a temperature of 180°C for 18 h to obtain a MgAl-LDHs suspension;
[0050] 2) Take 9 mL of tetraethyl orthosilicate, mix the suspension and tetraethyl orthosilicate in a volume ratio of 20:3, add 5 g of sodium hydroxide, 3 g of F127 and 1.5 g of CTAB, and stir well to mix.
[0051] 3) The obtained mixed solution was subjected to spray pyrolysis using ultrasonic atomization with an atomization frequency of 1.7 MHz and a power of 50 W. The micro-droplets generated by the atomization were introduced into a tubular furnace for high-temperature pyrolysis treatment. The heating area was 30 cm long and the temperature was 700°C. The powder was collected and vacuum dried at 100°C for 16 h to finally obtain SiO2-coated MgAl-LDHs nanocomposite flame retardant.
[0052] Example 3
[0053] A method for preparing a highly flame-retardant powder coating for new energy vehicles, specifically comprising:
[0054] According to mass parts, 100 parts of E-12 epoxy resin, 100 parts of unsaturated polyester resin, 30 parts of high-gloss calcium, 20 parts of SiO2-coated CaAl-LDHs nano-composite flame retardant, 7.5 parts of titanium dioxide and 15 parts of additives (the additives include leveling agent, dispersant, curing agent, and each additive is equal) are put into a mixing tank and stirred thoroughly; then the evenly stirred raw materials are extruded and formed by an extruder, the screw speed of the extruder is controlled to 300r / min, the temperature is controlled to 120°C, and a disperser is used for dispersion, and the dispersed powder coating is dried on a fluidized bed, and then ground with a grinder, and a high flame retardant powder coating is obtained after sieving and grading.
[0055] The preparation steps of the SiO2-coated CaAl-LDHs nanocomposite flame retardant used in Example 3 are as follows:
[0056] 1) Calcium nitrate and aluminum nitrate precursors with a mass ratio of 1:2 were dissolved in 20 mL of deionized water, and the concentration of calcium nitrate was 1 mol / L; 40 mL of ammonia water was then added, and the resulting solution was transferred into a high-pressure reactor with a polytetrafluoroethylene liner, the hydrothermal crystallization temperature was 220°C, and the hydrothermal reaction time was 12 h to obtain a CaAl-LDHs suspension;
[0057] 2) Take 9 mL of tetraethyl orthosilicate, mix the suspension and tetraethyl orthosilicate in a volume ratio of 20:3, add 5 g of sodium hydroxide, 3 g of F127 and 1.5 g of CTAB, and stir well to mix.
[0058] 3) The obtained mixed solution was subjected to spray pyrolysis using ultrasonic atomization with an atomization frequency of 1.7 MHz and a power of 50 W. The micro-droplets generated by the atomization were introduced into a tubular furnace for high-temperature pyrolysis treatment. The heating area was 30 cm long and the temperature was 600°C. The powder was collected and vacuum dried at a temperature of 100°C for 16 h to finally obtain SiO2-coated CaAl-LDHs nanocomposite flame retardant.
[0059] Comparative Example 1
[0060] A highly flame-retardant powder coating for new energy vehicles. Compared with Example 1, the flame retardant is replaced by an equal amount of ammonium polyphosphate flame retardant, Guangzhou Yinyuan New Materials Co., Ltd., FR-AP1012, and the other raw materials and preparation process remain unchanged.
[0061] Comparative Example 2
[0062] A highly flame-retardant powder coating for new energy vehicles. Compared with Example 1, the flame retardant is replaced by an equal amount of cyanuric acid melamine salt flame retardant, Guangzhou Yinyuan New Materials Co., Ltd., FR-MCA, and the other raw materials and preparation process remain unchanged.
[0063] Comparative Example 3
[0064] A highly flame retardant powder coating for new energy vehicles. Compared with Example 1, the flame retardant is replaced by an equal amount of tribromophenol flame retardant purchased from Jiangsu Rayne Environmental Protection Technology Co., Ltd., and the other raw materials and preparation process remain unchanged.
[0065] Comparative Example 4
[0066] A highly flame-retardant powder coating for new energy vehicles, in which the flame retardant is replaced with an equal amount of CoAl-LDHs flame retardant compared with Example 1, and the other raw materials and preparation process remain unchanged. The preparation process of CoAl-LDHs flame retardant is the same as that of Example 1, except that tetraethyl orthosilicate and sodium hydroxide are not added in the preparation.
[0067] Comparative Example 5
[0068] A highly flame-retardant powder coating for new energy vehicles, wherein the flame retardant is replaced with an equal amount of MgAl-LDHs flame retardant compared to Example 2, and the other raw materials and preparation process remain unchanged. The preparation steps of the MgAl-LDHs nano flame retardant are the same as those of Example 2, except that tetraethyl orthosilicate and sodium hydroxide are not added during the preparation.
[0069] Comparative Example 6
[0070] A highly flame-retardant powder coating for new energy vehicles, wherein the flame retardant is replaced by an equal amount of CaAl-LDHs flame retardant compared to Example 3, and the other raw materials and preparation process remain unchanged. The preparation steps of the CaAl-LDHs nano flame retardant are the same as those of Example 3, except that tetraethyl orthosilicate and sodium hydroxide are not added during the preparation.
[0071] Comparative Example 7
[0072] A highly flame-retardant powder coating for new energy vehicles, compared with Example 1, does not add a flame retardant, and other raw materials and preparation processes remain unchanged.
[0073] The high flame retardant powder coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were subjected to performance tests:
[0074] 1. Conventional performance test
[0075] According to HG / T2006-2006 standard, the gel time, film appearance, film thickness, hardness, adhesion, impact resistance, bending resistance, gloss, alkali resistance, acid resistance, boiling water resistance, heat resistance, artificial aging resistance and other conventional properties of high flame retardant powder coatings are tested.
[0076] Tensile performance test: Tested according to ISO527-2 standard, the test rate is 50mm / min. Bending performance test: Tested according to ISO178 standard, the test rate is 2mm / min. Impact performance test: Tested according to ISO179-1 standard.
[0077] Corrosion resistance test is carried out according to GB1763-89 standard.
[0078] Table 1 Performance test table of powder coatings prepared in Examples 1-3 and Comparative Examples 1-6
[0079]
[0080]
[0081] 2. Flame retardant performance test:
[0082] The powder coating samples obtained from Example 1 to Example 3 and Comparative Example 1 to Comparative Example 7 were pressed into sheets by an extruder, and then directly burned to determine the oxygen index. The oxygen index was evaluated with reference to GB / T2406.2-2009 standard, and the fire resistance was determined according to GB14907-2018 standard. The results are shown in Table 2.
[0083] Table 2 Flame retardant performance test table of powder coatings prepared in Examples 1-4 and Comparative Examples 1-7
[0084]
[0085] As can be seen from Table 1, compared with the powder coating of the comparative example, the high flame retardant powder coating of the embodiment has little effect on the conventional properties of the embodiment by changing the type and amount of the flame retardant. However, by changing the type and amount of the flame retardant, especially by using the SiO2-coated layered dihydrogen double hydroxide nanocomposite flame retardant, the oxygen index and GB14907 fire resistance of the embodiment are significantly better than those of the comparative example, showing excellent flame retardant properties.
[0086] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A highly flame retardant powder coating for new energy vehicles, characterized in that: The high flame retardant powder coating for new energy vehicles includes the following raw materials in parts by weight: 80 to 150 parts of epoxy resin, 50 to 110 parts of unsaturated polyester resin, 15 to 50 parts of filler, 5 to 30 parts of flame retardant, 2 to 7.5 parts of pigment, and 10 to 25 parts of auxiliary agent; the flame retardant is a silicon oxide-coated layered double hydroxide nanocomposite flame retardant.
2. The highly flame retardant powder coating for new energy vehicles according to claim 1, characterized in that: The composite nano flame retardant preparation method comprises the following steps: 1) preparing a suspension of layered double hydroxide by a hydrothermal crystallization method; 2) mixing the suspension with tetraethyl orthosilicate, sodium hydroxide, a surfactant, and a structure directing agent to obtain a mixed solution; 3) spraying the mixed solution for pyrolysis and vacuum drying to obtain a silicon oxide-coated layered double hydroxide nanocomposite flame retardant.
3. The highly flame retardant powder coating for new energy vehicles according to claim 2, characterized in that: In step 1), the layered double hydroxide is one of CoAl-LDHs, MgAl-LDHs and CaAl-LDHs; the temperature of the hydrothermal crystallization method is 150-220° C., and the hydrothermal reaction time is 12-24 hours.
4. The highly flame retardant powder coating for new energy vehicles according to claim 2, characterized in that: In step 2), the volume ratio of the suspension to tetraethyl orthosilicate is 20:3, and the mass ratio of sodium hydroxide, surfactant and structure directing agent is 10:6:
3.
5. The highly flame retardant powder coating for new energy vehicles according to claim 2 or 4, characterized in that: In step 2), the surfactant is F127; and the structure directing agent is CTAB.
6. The highly flame retardant powder coating for new energy vehicles according to claim 2, characterized in that: In step 3), the spray pyrolysis is specifically: ultrasonic atomization is used, the atomization frequency is 1.7 MHz, the power is 50 W, the micro droplets generated by atomization are introduced into a tubular furnace for high-temperature pyrolysis treatment, the heating area length is 30 cm, the temperature is 600-800° C., and the powder is collected.
7. The highly flame retardant powder coating for new energy vehicles according to any one of claims 1 to 6, characterized in that: The high flame retardant powder coating for new energy vehicles has an oxygen index of 46 to 55 and a GB14907 fire resistance of 1.12 to 1.35 hours.
8. A method for preparing a highly flame-retardant powder coating for new energy vehicles according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: adding a formulated amount of epoxy resin, unsaturated polyester resin, filler, flame retardant, pigment and additive into a mixing tank, fully stirring and mixing, extruding, dispersing, drying, grinding, screening and grading to obtain a highly flame retardant powder coating for new energy vehicles.
9. An application of a highly flame retardant powder coating for new energy vehicles according to any one of claims 1 to 7, characterized in that: Used in new energy vehicles.
Citation Information
Patent Citations
Method for preparing mesoporous silicon dioxide micro-sphere by combined template method
CN101214962A
Impact-resistant fireproof electronic component powder coating and preparation method thereof
CN106167666A
High performance flame retardant powder coating
CN109207018A
High-performance powder coating for insulating coating of new energy automobile battery and production process of high-performance powder coating
CN117165145A
Process for modifying inorganic oxygen-containing particulate material, product obtained therefrom, and use thereof
US20100179249A1